Implementation of PI Controller for 3ф BLDCM Drive Using FPGA - S.M. Ramesh Balaji; C. Muniraj (International Journal of Reconfigurable and Embedded Systems (IJRES), 2015)
Despite the need of a complex motor controller, the simple construction of BLDC motors offers several inherent advantages not provided with brushed DC motors in terms of low inertia, high torque and a very wide speed range. The BLDC motors include, Longer service life due to a lack of electrical and friction losses and also free maintenance due to a lack of brushes and mechanical commutators. The EMI and noise are reduced because of the elimination of ionizing spikes from brushes. The control system of BLDCM is highly complex drive due to nonlinear nature. In such a system for implementing control algorithm needs high speed processor. In this work the controller Xilinx Spartan-6 FPGA is a demonstration platform intended to become familiar with the new features and availability of the Spartan-6 FPGA. The various experimental tests are carried out in 3Ф BLDCM .The experimental results are reported in order to verify the steady state, transient and robustness performance of the controller.